EmFORE: Learning Email Folder Classification Rules by Demonstration - Singh, Mukul; Cambronero, José; Gulwani, Sumit; Le, Vu; Verbruggen, Gust (38th Annual AAAI Conference on Artificial Intelligence - Demo Track, 2024)
Tools that help with email folder management are limited, as users have to manually write rules to assign emails to folders. We present EMFORE, an iterative learning system that automatically learns and updates such rules from observations. EMFORE is fast enough to suggest and update rules in real time and suppresses mails with low confidence to reduce the number of false positives. EMFORE can use different rule grammars, and thus be adapted to different clients, without changing the user experience. Previous methods do not learn rules, require complete retraining or multiple new examples after making a mistake, and do not distinguish between inbox and other folders. EMFORE learns rules incrementally and can make the neutral decision of leaving emails in the inbox, making it an ideal candidate for integration in email clients.